The Art of Digital Curation: Co-operative Stewardship of Net-Based Art - Post, Colin (Archivaria, 2021)
Artists have long engaged with digital and networked technologies in critical and creative ways to explore both new art forms and novel ways of disseminating artworks. Net-based artworks are often created with the intent to circulate outside traditional institutional spaces, and many are shared via artist-run platforms that involve curatorial practices distinct from those of museums or commercial galleries. This article focuses on a particular artist-run platform called Paper-Thin, characterizing the activities involved in managing the platform as digital curation in a polysemous sense – as both the curation of digital artworks and the stewardship of digital information in a complex technological ecosystem. While scholars and cultural heritage professionals have developed innovative preservation strategies for digital and new media artworks housed in institutional collections, the ongoing care of artworks shared through networked alternative spaces is largely carried out co-operatively by the artists and curators of these platforms. Drawing on Howard Becker’s sociological theory of art worlds as networks of co-operative actors, this article describes the patterns of co-operative work involved in creating, exhibiting, and then caring for Net-based art. The article outlines the importance, for cultural heritage professionals, of understanding the digital-curation practices of artists, as these artist-run networked platforms demonstrate emergent approaches to the stewardship of digital culture that move beyond a custodial paradigm. RÉSUMÉ Les artistes utilisent depuis longtemps les technologies numériques et en réseau de manière critique et créative pour explorer de nouvelles formes d’art et de nouveaux modes de diffusion des oeuvres d’art. Les oeuvres d’art en ligne sont souvent créées dans l’intention de les voir circuler en dehors des espaces institutionnels traditionnels, et nombre d’entre elles sont partagées via des plateformes gérées par des artistes, lesquelles nécessitent des pratiques de conservation différentes de celles des musées ou des galeries commerciales. Cet article se penche sur une plateforme spécifique gérée par des artistes appelée Paper-Thin et qualifie les activités impliquées dans la gestion de la plateforme de conservation numérique dans un sens polysémique – à la fois la conservation d’oeuvres d’art numériques et l’intendance de l’information numérique dans un écosystème technologique complexe. Alors que les universitaires et les professionnels du patrimoine culturel ont développé des stratégies de préservation innovantes pour les oeuvres d’art numériques et sur nouveaux médias conservés dans des collections institutionnelles, l’entretien continu des oeuvres d’art partagées via ces espaces alternatifs en réseau est en grande partie réalisé conjointement par les artistes et les conservateurs de ces plateformes. S’inspirant de la théorie sociologique d’Howard Becker sur les mondes de l’art comme réseaux d’acteurs coopératifs, cet article décrit les schémas du travail coopératif engagés dans la création, l’exposition et l’entretien de l’art en ligne. L’article souligne l’importance, pour les professionnels du patrimoine culturel, de comprendre les pratiques de curation numérique des artistes, car ces plateformes en réseau gérées par des artistes démontrent des approches émergentes de l’intendance de la culture numérique qui vont au-delà du paradigme de la conservation.